GE_GERICHTE P/8308/2019 vom 31. März 2022 - GE Cour de justice (2022)
SÉQUESTRE(MESURE PROVISIONNELLE);PART DE COPROPRIÉTÉ;SOUPÇON;ABUS DE CONFIANCE;ESCROQUERIE;PROPORTIONNALITÉ | CP.71.al3; CP.138; CP.146